Time-calibrated phylogeny of neotropical freshwater fishes - Tagliacollo, Victor A.; Tan, Milton; Reis, Roberto E.; Gaia, Ronielson; Carrijo, Virgilio; Ranuzi, Marcelo; Craig, Jack M.; Albert, James S. (Frontiers in Bioinformatics, 2024)
Neotropical Freshwater Fish (NFF) fauna exhibits the greatest phenotypic disparity and species richness among all continental aquatic vertebrate faunas, with more than 6,345 species distributed across the mostly tropical regions of Central and South America. The last two decades have seen a proliferation of molecular phylogenies, often at the species level, covering almost all 875 valid NFF genera. This study presents the most comprehensive genome-wide, time-calibrated phylogenetic hypothesis of NFF species to date, based on DNA sequences generated over decades through the collaborative efforts of the multinational ichthyological research community. Our purpose is to build and curate an extensive molecular dataset allowing researchers to evaluate macroevolutionary hypotheses in the NFF while facilitating continuous refinement and expansion. Using thousands of DNA sequences from dozens of studies, we compiled a supermatrix of 51 markers for 5,984 taxa, representing 3,167 NFF species. Based on this dataset, we built the most species-rich time-calibrated phylogeny of the NFF taxa to date, summarizing the collective efforts of the ichthyological research community since the midpoint of the last century. We provide a summary review of this remarkable evolutionary history and hope this dataset provides a framework for forthcoming studies of the NFF fauna, documenting compelling, emergent patterns in the world’s most diverse continental vertebrate fauna.